Ethical issues with regard to truth-telling in medical practice [Tip uygulamalarinda gerçeǧin söylenmesine ilişkin etik sorunlar] - (:unkn) unknown (My University, 2008)
Several issues such as disclosing medical professionals' errors to patients, use of placebos for therapeutic purposes, and providing patients diagnostic and prognostic information with regard to incurable diseases or diseases with a poor prognosis have been evaluated within the topic known as "truth-telling" in medical ethics literature. Until recently, a paternalistic approach where the physician typically acted as the decision maker has prevailed in medical practice and comprehensive disclosure to patients about their diagnosis and prognosis has almost no place in the patient-physician tradition of the past. However, radical changes were observed in this traditional approach and paternalistic views have been seriously challenged, starting from the second half of the 20th century. Consequently, views on truth-telling and their reflections in medical practice were also significantly affected, and ethical issues with regard to truth-telling have been examined in detail. Yet, research on these issues in Turkey is very limited and the views presented by some of the authors in the field, as well as the views of the relevant legislative texts appear to adopt the paternalistic tradition. For this reason, this paper aims to focus on ethical problems with regard to truth-telling in medical practice and their solutions in the light of the recent views in the medical ethics literature. In addition, the relevant provisions in the legislative texts and the available results of the studies performed in Turkey have also been provided and compared with the current views in medical ethics.